Number of translations and translation direction in masked translation priming: evidence from unbalanced English–Chinese bilinguals - Zhao, Quanbei; Li, Jia; Xiong, Wenxin; Xing, Hongbing (Frontiers in Psychology, 2024)
Within the research field of bilingual lexical representation and organization, much attention has been given to whether two languages share a conceptual system and what factors modulate the connection between this conceptual system and the lexical systems of a bilingual’s L1 and L2. One of the most valid ways in the psycholinguistics domain to explore these doubts is to examine the masked translation priming effect and the priming asymmetry through cross-language priming experiments. In this study, a masked priming lexical decision task was conducted with unbalanced English-Chinese bilinguals to investigate whether the masked translation priming effect exists in both translation directions, and to further reveal how the number of translations, which can be categorized into one-translation pair and more-than-one-translation pair conditions, affects the priming effects and modulates translation priming asymmetry. It was demonstrated that both translation direction and the number of translations influence the priming effect. Specifically, the priming effect was observable from L1 to L2 but not from L2 to L1, and the priming for one-translation pairs was significantly greater when compared to that for more-than-one-translation pairs. Moreover, the impacts of translation direction on the priming effect differed between the one-translation pair and more-than-one-translation pair conditions: under the former condition, substantial priming occurred in both directions, whereas for the latter condition, it was observed only in the L1–L2 direction. Several models of the bilingual mental lexicon, mainly the Revised Hierarchical Model and the Distributed Conceptual Feature Model, were used to elucidate the above results.